Pengaruh E-Service Quality, E-Trust, dan Brand Image terhadap Loyalitas Pelanggan pada Pengguna Aplikasi BYOND by BSI di Wilayah Balikpapan Kota - Maharani Syahputri; Dewi Sartika (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This research aims to identify both the partial and simultaneous positive and significant effects of e-service quality, e-trust, and brand image on the customer loyalty of Byond by BSI users in Balikpapan City. The study adopts a quantitative correlational method. A total of 100 respondents were selected using a purposive sampling technique. Data were collected through online questionnaires distributed via a Google Form link. The analytical procedures utilized include correlational analysis, instrument tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using IBM SPSS Statistics version 24. The results of the study indicate that, partially, e-service quality and e-trust variables each have a positive and significant effect on customer loyalty among users of the Byond by BSI application in Balikpapan City. Meanwhile, brand image variable has a positive but not significant effect on customer loyalty among users of the Byond by BSI application in Balikpapan City. Furthermore, when examined simultaneously, the three variables collectively show a positive and significant effect on customer loyalty of Byond by BSI applications users in Balikpapan City.